A Novel High-Linearity Microwave Photonic Link Based on the Strategy of Adding a Compensation Path Using a Bidirectional Phase Modulator - Tianwei Jiang; Ruihuan Wu; Song Yu; Dongsheng Wang; Wanyi Gu (IEEE Photonics Journal)
A novel phase-modulation direct-demodulation microwave photonic link for improving the spurious-free dynamic range (SFDR) is proposed and experimentally demonstrated. In the proposed system, two different C-band optical wavelengths are modulated by a phase modulator in opposite directions. After combining the wavelengths, a fiber Bragg grating (FBG) is used to remove the optical spectrum between the two wavelengths. Because of the natural and wideband $π$ phase difference between the up and low optical sidebands after the phase modulation, third-order intermodulation distortion (IMD3) can be counteracted by subtly designing the optical power and modulation depth relationships between the two wavelengths. The experimental results show that IMD3 is reduced by 28.6 dB, achieving an SFDR improvement of 20 dB compared to a traditional single sideband phase-modulation microwave photonic link.